Respuesta :

So,

Let x represent Joe's weight and y represent Jeff's weight.

"Joe weighs 20 lbs. less than twice Jeff's weight."
x = 2y - 20

"If Jeff would gain 10 lbs., then together they would weigh 250 lbs."
(y + 10) + x = 250

We now have our two open sentences.
x = 2y - 20
(y + 10) + x = 250

Get rid of parentheses.
x = 2y - 20
x + y + 10 = 250

We will use Elimination by Substitution.
2y - 20 + y + 10 = 250

Collect Like Terms.
3y - 10 = 250

Add 10 to both sides.
3y = 260

Divide both sides by 3.
[tex]Jeff's\ weight = 86 \frac{2}{3} \ lbs.[/tex]

Substitute again.
[tex]x = 2(86 \frac{2}{3} )-20[/tex]

Multiply.
[tex]x = 173 \frac{1}{3} -20[/tex]

Subtract.
[tex]Joe's\ weight = 153 \frac{1}{3}\ lbs.[/tex]

Check.

"Joe weighs 20 lbs. less than twice Jeff's weight."
Jeff's weight times two is 173 and one-third.
20 lbs. less than that is 153 and one-third lbs. Check.

"If Jeff would gain 10 lbs., then together they would weigh 250 lbs."
86 and two-thirds + 10 = 96 and two-thirds.
96 and two-thirds + 153 and one-third equals 250 lbs. Check.

[tex]Joe's\ weight\ is\ 153 \frac{1}{3} \ lbs.[/tex]
[tex]Jeff's\ weight\ is\ 86 \frac{2}{3} \ lbs.[/tex]